Nutritional Knowledge and Health Behaviour Related to CVD, Narrative Review: Nutritional Knowledge and Health Behaviour Related to CVD - Saeed, Anam (Pakistan Journal of Health Sciences, 2025)
Cardiovascular disease is the leading cause of death worldwide. A person’s diet plays a critical role in their cardiovascular health and is linked to the progression of heart-related diseases. Several scientific researchers have demonstrated an association between dietary habits, lifestyle, and Cardiac diseases. This narrative review aims to demonstrate the present state of scientific evidence on nutritional knowledge and health behaviour related to CVD (Cardiovascular Diseases). The review focuses on the impact of dietary patterns and lifestyle on the risk factors of CVD, summarizing facts from surveys, population-related scientific trials, observational research, and meta-analyses. Unhealthy dietary behaviours and lifestyle, for instance, high consumption of saturated fatty acids, red and processed meat, refined carbohydrates, sugar-sweetened beverages and excessive salt, have been related to an amplified possibility of CVD. On the contrary, increasing consumption of a plant-centred diet, such as food fiber, fruits, vegetables, and nuts, has been shown to reduce CVD risk-related factors. The Mediterranean diet is considered to be a well-supported dietary pattern for prevention. This review offers novel understandings into diet-related factors that are either harmful or beneficial in the context of CVD and suggests potential strategies for improving cardiovascular health. The implications of these findings put forward a need for healthcare providers to enhance their discussions with female patients about CHD, providing targeted education on its prevention.